Effects of electroacupuncture on pediatric chronic urinary retention: a case-series study - Yang, Min; Gao, Shuai; Yao, Hao; He, Xin; Fang, Jiufei; Chen, Yu; Liu, Zhishun (Frontiers in Pediatrics, 2023)
Objectives: This study aims to preliminarily evaluate the effect and safety of electroacupuncture (EA) in treating pediatric chronic urinary retention (CUR) following lumbosacral surgeries, with treatment duration evaluated. Methods: This prospective case-series study was performed from August 5, 2019, to July 31, 2022. Pediatric patients diagnosed with CUR following lumbosacral surgeries were included and treated by EA for 2 to 16 weeks. Responders were defined as participants achieving a reduction of 50% or more in post void residuals (PVR) from baseline. Time-to-event analysis was applied to explore the association between EA treatment duration and response rate. Adverse event was recorded. Results: Totally 14 participants (mean [SD] age,12[4] years) completed EA treatment. Response rate was 71% (10/14) at the 12nd week. 50% (7/14) of participants removed catheters at the 12nd week, and none of them experienced re-catheterization in the 24-week follow-up. No serious adverse event was reported. Time-to-event analysis estimated that over 50% patients could respond to EA of more than 8 weeks. Subgroup analysis showed that participants with baseline PVR ≥ 300ml and CUR duration ≥ 12 months experienced longer EA duration to reach the response rate of 50%, compared with those whose PVR < 300ml and CUR duration < 12 months (median value: 12 weeks vs 8 weeks, 12 weeks vs 4 weeks, respectively). Conclusions: EA could reduce PVR for pediatric patients suffering from CUR following lumbosacral surgeries, with long-term efficacy and safety. EA treatment of more than 8 weeks was reasonable. Further study of a larger sample and controlling is needed.